Penerapan Keadilan Restoratif Di Kejaksaan Sebagai Perlindungan Korban Kekerasan Dalam Rumah Tangga - Meylana, Hendra; Asphianto, Aan (Universitas Sultan Ageng Tirtayasa, 2024)
The implementation of restorative justice in the prosecutor's office has been carried out, one of which is in cases of domestic violence. The purpose of this research is to examine the application of restorative justice by the prosecutor's office in realizing protection for victims of domestic violence. The research method uses normative legal research with a case approach and qualitative descriptive analysis. The results of the study found that the application of restorative justice in the prosecutor's office in handling cases of domestic violence can protect victims because the process is carried out with mediation between the victim and the perpetrator, so that the victim can convey his wishes and needs facilitated by the prosecutor. Victims benefit from the law enforcement process and reduce the accumulation of cases in court.